h.hofstede (h.hofstede@hogeland.nl)

 
1. (p - 1)! = -1 (mod p)     (stelling van Wilson)
p
(p - 1)! = -p (mod p2)   want  (-1 + kp) vermenigvuldigen met p geeft  -p + kp2
p!  = -p (mod p2)
p
! + p = 0  mod(p2)
Dus is  p! + p deelbaar door  p2    
       
2. Gebruik de stelling:   (k - 1)!  (p - k)!    (-1)k  (mod p)   met  p = 11:

k = 1  geeft  0! 10! = (-1)1  (mod 11) =  -1  (mod 11)
k = 2  geeft  1! 9! = (-1)2  (mod 11) = 1 (mod 11)
k = 3  geeft  2! 8! = (-1)3  (mod 11) = -1 (mod 11)
k = 4  geeft  3! 7! = (-1)4  (mod 11) = 1  (mod 11)
k = 5  geeft  4! 6!  = (-1)5 (mod 11) = -1  (mod 11)
5! = 120 = -1  (mod 11)

Alles met elkaar vermenigvuldigd:
0! 1! 2! ... 10!  = -1 1 -1 1 -1 -1  =  1 (mod 11)  
       

h.hofstede (h.hofstede@hogeland.nl)